Identifying and detecting potentially adverse ecological outcomes associated with the release of gene-drive modified organisms. (24th January 2018) - Hayes, Keith R.; Hosack, Geoffrey R.; Dana, Genya V.; Foster, Scott D.; Ford, Jessica H.; Thresher, Ron; Ickowicz, Adrien; Peel, David; Tizard, Mark; De Barro, Paul; Strive, Tanja; Dambacher, Jeffrey M.
ABSTRACT: Synthetic gene drives could provide new solutions to a range of old problems such as controlling vector-borne diseases, agricultural pests and invasive species. In this paper, we outline methods to identify hazards and detect potentially adverse ecological outcomes at the individual (genotype, phenotype), population, community and ecosystem level, when progressing Gene Drive Modified Organisms through a phased test and release pathway. We discuss the strengths and weaknesses of checklists and structured hazard analysis techniques, identify methods to help meet some of the challenges of detecting adverse ecological outcomes in experiments and confined field trials, and discuss ways to improve the efficiency and statistical rigour of post-release monitoring strategies.